2009
DOI: 10.1177/0010414009332128
|View full text |Cite
|
Sign up to set email alerts
|

Making Reconstruction Work: Civil Society and Information after War’s End

Abstract: This article develops and tests a general framework for explaining variations in the extent of postwar reconstruction. Existing studies point to the importance of economic resources and a coherent state apparatus in promoting effective reconstruction. This study argues that because reconstruction inherently requires coordination between numerous societal actors as well as between state and society, a full explanation for the extent of reconstruction must examine the linkages among those actors, especially civi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Dynes (2005) has suggested, based on experiences of survivors in a number of disasters, that social capital may be the basis for resilience as it provides information and resources at a critical moment. In one of the first quantitative tests of civil society's role in regional rehabilitation, Kage (2010) demonstrates that following World War II, Japanese prefectures with more vibrant civil society (measured through higher levels of communication) recovered more quickly.…”
Section: Social Capital and Disaster Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Dynes (2005) has suggested, based on experiences of survivors in a number of disasters, that social capital may be the basis for resilience as it provides information and resources at a critical moment. In one of the first quantitative tests of civil society's role in regional rehabilitation, Kage (2010) demonstrates that following World War II, Japanese prefectures with more vibrant civil society (measured through higher levels of communication) recovered more quickly.…”
Section: Social Capital and Disaster Recoverymentioning
confidence: 99%
“…analyses to test them. 1 Most studies investigating social capital and disaster have relied on qualitative and impressionistic evidence from a few cases (Buckland and Rahman, 1999;Nakagawa and Shaw, 2004;Dynes, 2005) or quantitative evidence from individuallevel surveys (Tatsuki and Hayashi, 2002;Tatsuki, 2008); only recently have scholars integrated social capital measures into a quantitative study of rehabilitation (Kage, 2010). This paper builds on these initial findings and uses data on whole neighbourhoods affected by the 1923 Kanto earthquake that leveled 40 per cent of Tokyo to test five factors that may influence the pace of population recovery.…”
mentioning
confidence: 99%
“…(Kage, 2010; Chamlee-Wright, 2010; Allen, 2006; Beaudoin, 2007; Dynes, 2006; Hausman, Hanlon, & Seals, 2007; Koh & Cadigan, 2008; Mathbor, 2007; Moore et al, 2004; Nakagawa & Shaw, 2004; Pelling, 1998; Buckland & Rahman, 1999) Examining social capital and its relationship to disaster preparedness has grown in prominence partially due to world-wide need to more effectively and proactively respond to terrorist attacks, viral epidemics, or natural disasters. (Aldrich, 2012a; Aldrich, 2012b; Koh & Cadigan, 2008; Ada & Bolat, 2010) Also the focus on social capital is a result of its strong predictive power in effective disaster response and recovery at the community and individual levels.…”
Section: Introductionmentioning
confidence: 99%
“…(Chamlee-Wright, 2010; Aldrich, 2010a; Aldrich, 2010b; Aldrich & Crook, 2008; Kage, 2010) These studies have demonstrated that women, children, the elderly, those of lower social status, and other marginalized communities are vulnerable during and after disaster strikes because they are often unable to penetrate the social networks to access aid in the same way or at the same rate as non-marginalized populations. (Buckland & Rahman, 1999; Beaudoin, 2007; Dynes, 2006; Hawkins & Maurer, 2010; Aldrich & Crook, 2008; Aldrich, 2010a; Aldrich, 2010b; Aldrich, 2011b; Aldrich, 2011c; Aldrich, 2012a; Aldrich, 2012c)…”
Section: Introductionmentioning
confidence: 99%
“…The placement of temporary FEMA trailers in New Orleans after Hurricane Katrina was strongly correlated with neighborhood levels of social capital (Aldrich and Crook 2008). New studies involving both qualitative and quantitative methods demonstrate that higher levels of social capital bring with them better mobilization, coordination, and trust, and these in turn lead to more rapid and effective recoveries (Chamlee-Wright 2010; Kage 2010).…”
Section: Between Market and State: Social Networkmentioning
confidence: 99%